The Relevance of Buddhist Perspectives to Political Science Education - Phuyal, Shyam Prasad (Tribhuvan University Journal, 2022)
Buddhism aspires to impart truthfulness, beauty, morality, kindness, contentment, and enlightenment in its believers. Buddhism’s primary teachings may also provide viewpoints for political science courses. The main objective of this paper is to identify human values and social values in modern society as the essence of Buddhist teachings that are significant in Political Science Education and modern civilization. As a review paper, this paper contains a comprehensive introduction to Buddhism, its basis, teaching methods, and educational approaches. The paper extensively uses secondary data in its methodology. The data were analyzed using the content analysis method, and the findings were discussed as the themes that emerged. Then, a contemplative conclusion on Buddhist teaching and its pedagogical components is included. The major implications of Buddhism for Political Science Education have been indicated. The conclusion is then that Buddhism provides such constructs for education as personal freedom, intelligence, wisdom, moral, talent, non-violence and the secular persons, and that it can be a significant source of the curricular contents for Political Science Education.